2023
DOI: 10.1177/23259671221147921
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Assessment of the Quality and Comprehensibility of YouTube Content on Ulnar Collateral Ligament Injury and Management

Abstract: Background: Ulnar collateral ligament (UCL) reconstruction has received a unique level of attention in the press and social media. There has also been an increasing use of the internet by patients to seek medical information. Concern exists regarding the quality and comprehensibility of online information when used for patient education. Purpose: To evaluate the quality and comprehensibility of the most-viewed YouTube videos related to the diagnosis and management of UCL injuries. Based on our new evidence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A total of 70 videos were evaluated; only 64 met the inclusion criteria, similar to a study evaluating YouTube video content quality for medical education purposes by Mutlu and Arik that used 65 videos [ 5 ]. In other studies, Batar et al used 52 videos, Crutchfield et al used 142 videos, Di Bello et al 156 videos, and Desai et al 92 videos that met inclusion criteria [ 6 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 70 videos were evaluated; only 64 met the inclusion criteria, similar to a study evaluating YouTube video content quality for medical education purposes by Mutlu and Arik that used 65 videos [ 5 ]. In other studies, Batar et al used 52 videos, Crutchfield et al used 142 videos, Di Bello et al 156 videos, and Desai et al 92 videos that met inclusion criteria [ 6 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the majority of the uploaded videos 92.2% (n=59) were more than one year old compared to the remaining videos that were more than one week to one year old 7.8% (n=5). In similar studies, there was less emphasis on the publishing time of the video and more focus on content quality [ 5 - 9 ]. Since most of the videos were over a year old, this might imply the potential for physicians, hospitals, and health organizations to use YouTube more efficiently to provide timely information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations